Hubungan Kepatuhan Perawat Kamar Bedah dalam Penerapan SPO Surgical Safety Checklist (SSC) dengan Keselamatan Pasien Operasi di Instalasi Bedah Sentral RSUD Waluyo Jati Kraksaan - Muh. Audini Mukhlisiddin; Iin Aini Isnawati; Grido Handoko Sriyono (STIKes Ibnu Sina Ajibarang, 2023)
The Surgical Safety Checklist is a checklist designed to ensure safe and high-quality surgeries for patients. This research aims to determine the Relationship Between Operating Room Nurses' Compliance in Implementing the Surgical Safety Checklist (SSC) and Patient Safety in Surgical Procedures at the Central Surgery Department of the Waluyo Jati District General Hospital in Probolinggo.The research method employed in this study Was Analytical Observational with a Cross-Sectional approach, involving a sample of 25 respondents selected through total sampling technique. The research results revealed that the majority of respondents exhibited a high level of compliance in implementing the Surgical Safety Checklist (SSC) in the compliant category, with 23 respondents (92%). Similarly, the majority of respondents achieved a high level of patient safety in surgical procedures, with 23 respondents (92%) meeting the criteria. The Fisher's Exact Test analysis yielded a significance value of α < 0.05, specifically (0.003), indicating a significant Cornelation between the compliance of Operating Room Nurses in the implementation of the SSC and the safety of surgical patients in the Central Surgery Unit of Waluyo Jati General Hospital, Probolinggo. Each nurse should have personal awareness and responsibility to adhere to the SSC. For respondents who are not compliant, the hospital should consider providing training and supervision by nursing department heads to enhance compliance with the SSC. .